Non-descent vaginal hysterectomy surgery associated with less complications and good prognosis - Pranita Somani; Priyanka Singh; Mangala Shinde (Asian Journal of Medical Sciences, 2022)
Background: Removal of the uterus through vagina when performed in a case without uterine descent or prolapse is known as “non-descent vaginal hysterectomy” or NDVH. Vaginal route is preferred as compared to laparoscopic and abdominal methods. The advantages of vaginal hysterectomy being fewer complications, less post-operative stay, cost effective, and useful in bulky uterus. Aims and Objectives: The aims of the study were as follows: (1) To study the intraoperative and post-operative complications encountered during NDVH and their management. (2) To assess the intraoperative blood loss, the operative time, and post-operative hospital stay. (3) To study and check the feasibility of vaginal route as the primary route for all hysterectomies in the absence of uterine prolapse. Materials and Methods: A total of 50 patients were included in the study. Detailed history was taken including obstetric history and menstrual history and clinical examination was performed. After taking written, informed consent and doing proper pre-operative preparation, the patient was posted for NDVH. Post-operative complications were noted. Patients were asked to come for follow-up after 15 days. Results: In 92% of cases operated, no intraoperative complications were found suggesting low morbidity associated with the procedure. Hemorrhage requiring blood transfusion was found in 4% of cases. Average operative time was 61.2 ± 27.89 min, average blood loss was 170 ± 81.44 ml, and average hospital stay was 5.94 ± 4.95 days. On histopathological examination, 40% were having leiomyoma and dysfunctional uterine bleeding was seen in 22% of cases. Pain was the most common complication seen in 30% of cases while vaginal discharge was seen in just 4% of cases. About 80% of patients were discharged on post-operative day 5. Conclusion: In 92% of NDVH cases, no intraoperative complications were found suggesting low morbidity associated with the procedure. The post-operative hospital stay was restricted to 5 days in 80% of cases which indicates early discharge of the patient. Post-operative complications such as vaginal discharge and fever were seen only in 4% of cases. NDVH should, therefore, be considered as the primary route for all hysterectomies unless contraindicated in the absence of prolapse.